Implementation of Multilayer Perceptron for Image Classification - Salma, Amnia (Proceeding International Conference on Science and Engineering, 2021)
Abstract. This research proposed to classify images on hands playing rockpaperscissor through hand images. We use Multi Layer Perceptron to classify. There are there class for the classification which are rock class, paper class and scissor class. Dataset for this research obtained from Kaggle Dataset. The number of datasets is 2188 images which are 712 rock images, 726 paper images and 750 scissor images. The Accuracy of this model is very good arround 95%.